Sairaalan reaaliaikainen tilannekuva päivittäisessä johtamisessa - Mykkänen, Minna; Miettinen, Merja; Siponen, Tiina; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2021)
The study describes the formation of the hospital's real-time situation picture, situation awareness and situation understanding with the help of the organization's register data. The data is based on organizationally structured data resources. The research data were collected from patient administration data, the work shift program and the electronic patient record system. The data were analyzed by descriptive statistical methods. Based on the results, it is possible to form a real-time and visual situation picture of the entire hospital and an individual unit from different information systems into one entity. By interpreting the information, an understanding of the situation is formed, which gives an idea of how to act in the future. The data can also be used to develop the hospital's and unit's operations to support different levels of operational processes and decision-making. Electronic record systems for social and health care must be developed in such a way that they serve both the primary and secondary use of data at the same time.